2018
DOI: 10.1002/ajim.22875
|View full text |Cite
|
Sign up to set email alerts
|

Photokeratitis among restaurant workers: A case series

Abstract: This case report highlights the challenges associated with the diagnosis and workplace evaluation of occupationally acquired ultraviolet (UV) radiation-induced photokeratitis and associated skin burns in a group of restaurant workers. UV-C spectrum bulbs were inadvertently shipped and installed in insect light traps. Ocular and dermal symptoms were reported in 18 of 85 restaurant employees to varying degrees of severity over a 2-day period. One patient was formally diagnosed with a chemical burn/irritation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Stripp et al documented a case series of 18 employees at a restaurant with photokeratitis after exposure to UV-C spectrum light bulbs that were inadvertently shipped and installed in insect light traps. 24 Similar associations are documented after UV exposure at a night club 14 and in public gatherings within the vicinity of UV light sources with damaged protective covers. 12,13 Pertinent to our study, Leung and Ko reported a family of three adults with photokeratitis after exposure to a UV-C germicidal lamp early in the pandemic in Hong Kong.…”
Section: Discussionmentioning
confidence: 57%
“…Stripp et al documented a case series of 18 employees at a restaurant with photokeratitis after exposure to UV-C spectrum light bulbs that were inadvertently shipped and installed in insect light traps. 24 Similar associations are documented after UV exposure at a night club 14 and in public gatherings within the vicinity of UV light sources with damaged protective covers. 12,13 Pertinent to our study, Leung and Ko reported a family of three adults with photokeratitis after exposure to a UV-C germicidal lamp early in the pandemic in Hong Kong.…”
Section: Discussionmentioning
confidence: 57%
“…Also, a single ophthalmic image has been reported. UV exposure due to inappropriate installation of disinfection lamps in hospital coronary angiography unit, metal halide lamps in a gymnasium, UV-C–emitting insect-radiation traps in restaurants, mercury vapor lamps with vandalized protective covers in a livestock auction house, consumer-available germicidal UV lamps during the COVID-19 pandemic, and apron-disinfection lamps in poultry farms have been reported worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…UV‐C lamps are increasingly employed in multiple fields, such as healthcare and food industry, for their disinfectant properties. Cases of acute skin phototoxicity and photokeratitis after UV‐C exposure have already been reported, both in professional and domestic settings 2–5 . In most situations, the diagnosis was guided by an ophthalmologic examination, and UV‐C light source was quickly identified afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…Workstation survey performed in 2017 likely yielded no result because they were conducted during nonworking periods, with insecticide lamps turned off, thus making them difficult to identify.UV-C lamps are increasingly employed in multiple fields, such as healthcare and food industry, for their disinfectant properties. Cases of acute skin phototoxicity and photokeratitis after UV-C exposure have already been reported, both in professional and domestic settings [2][3][4][5]. In most situations, the diagnosis was guided by an ophthalmologic examination, and UV-C light source was quickly identified afterwards.Occupational UV-C burn may be a difficult diagnosis due to the lack of exposure awareness and must be evoked in the presence oferythema of uncovered parts with ophthalmological signs following an occupational rhythm.…”
mentioning
confidence: 99%